2009
DOI: 10.1073/pnas.0812942106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for electronic gap-driven metal-semiconductor transition in phase-change materials

Abstract: Phase-change materials are functionally important materials that can be thermally interconverted between metallic (crystalline) and semiconducting (amorphous) phases on a very short time scale.Although the interconversion appears to involve a change in local atomic coordination numbers, the electronic basis for this process is still unclear. Here, we demonstrate that in a nearly vacancy-free binary GeSb system where we can drive the phase change both thermally and, as we discover, by pressure, the transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 29 publications
3
33
0
Order By: Relevance
“…12 As-sputter-deposited films are amorphous metastable solid solutions. The threshold is clearly related to the well known explosive crystallization of bulk Sb near room temperature, 14 which at ambient pressure takes on a Peierls' distorted 15 A7 structure, and we have recently shown that Ge-Sb crystallizes in the same structure, 13 with Ge randomly occupying Sb lattice sites. %.…”
mentioning
confidence: 99%
“…12 As-sputter-deposited films are amorphous metastable solid solutions. The threshold is clearly related to the well known explosive crystallization of bulk Sb near room temperature, 14 which at ambient pressure takes on a Peierls' distorted 15 A7 structure, and we have recently shown that Ge-Sb crystallizes in the same structure, 13 with Ge randomly occupying Sb lattice sites. %.…”
mentioning
confidence: 99%
“…Additionally, similar phase change materials undergo an electronic driven transition. 29 To address the electronic system, transport measurements were done and the measured carrier concentration of a 50 nm film shown in Fig. 4(f) also exhibits a drastic change across the crystallization transition (measurements were taken at 1.9 K after each incremental annealing temperature).…”
mentioning
confidence: 99%
“…In any case, the PCM films studied here have p-type conductivity with Ge acting as a kind of dopant. 7 Furthermore, three types of samples were investigated, where different heating processes were used to achieve partial crystallization of the films (Fig. 1).…”
mentioning
confidence: 99%